2014
DOI: 10.1166/jnn.2014.8962
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ni–Mo/Al<SUB>2</SUB>O<SUB>3</SUB> Catalyst for Reverse Water Gas Shift (RWGS) Reaction

Abstract: In the present study, Mo/Al2O3 catalyst was prepared using impregnation method. Then it was promoted with Ni ions to produce Ni-Mo/Al2O3 catalyst. The structures of the catalysts were studied using X-ray diffraction (XRD), Energy dispersive X-ray (EDAX), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS), CO chemisorption, temperature programmed reduction of hydrogen (H2-TPR) and scanning electron microscope (SEM) techniques. Catalytic performances of the two catalysts were investigated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…At the higher temperature,t he 3wt% K-Mo 2 C/g-Al 2 O 3 resultsi n4 0.5 %c onversion and 98.2 %C Os electivity,w hich outperforms 2wt% K-Mo 2 C/g-Al 2 O 3 and the industrial ZnO/Al 2 O 3 and ZnO/Cr 2 O 3 catalysts. [16] Ac omparison of the catalysts used herein with other relevant catalysts is also included in Table 1a nd the Supporting Information to demonstrate the high selectivityo fK -Mo 2 C/ g-Al 2 O 3 .F urther reactor and spectroscopic studies are required [29] 17 34 N/A N/A 5.8 N/A Cu-Mo 2 C/250 8C [29] 13 40 N/A N/A 5.2 N/A Pd/Al 2 O 3 /260 8C [33] N/A 78 N/A N/A N/A N/A Mo/g-Al 2 O 3 /600 8C [34] 34.297 N/A N/A 32.1 N/A…”
Section: Resultsmentioning
confidence: 99%
“…At the higher temperature,t he 3wt% K-Mo 2 C/g-Al 2 O 3 resultsi n4 0.5 %c onversion and 98.2 %C Os electivity,w hich outperforms 2wt% K-Mo 2 C/g-Al 2 O 3 and the industrial ZnO/Al 2 O 3 and ZnO/Cr 2 O 3 catalysts. [16] Ac omparison of the catalysts used herein with other relevant catalysts is also included in Table 1a nd the Supporting Information to demonstrate the high selectivityo fK -Mo 2 C/ g-Al 2 O 3 .F urther reactor and spectroscopic studies are required [29] 17 34 N/A N/A 5.8 N/A Cu-Mo 2 C/250 8C [29] 13 40 N/A N/A 5.2 N/A Pd/Al 2 O 3 /260 8C [33] N/A 78 N/A N/A N/A N/A Mo/g-Al 2 O 3 /600 8C [34] 34.297 N/A N/A 32.1 N/A…”
Section: Resultsmentioning
confidence: 99%
“…Noble metal catalysts, mainly Pt and Rh based supported catalysts, have high activity towards hydrogen dissociation, relatively moderate strength with the adsorption of reaction intermediates and the incompletely filled D‐orbital electrons make them easier for the adsorption of reactants with moderate strength, which is further benefiting to form the intermediate “active compound” in RWGS reaction . Besides mentioned catalysts other metal catalysts as active components or as supports are Pd, Ni, Co, Fe, Fe supported on CNTs and carbide (Mo 2 C) catalyst …”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
“…Therefore, the improvement of the catalytic activity for the RWGS reaction can be ascribed to the change of catalyst structure and oxygen vacancies. Except for the above monometallic catalysts, some bimetallic catalysts-i.e., Pt-Co, Fe-Mo and Ni-Mo [25][26][27]-were also prepared and tested in the RWGS reaction. In general, the preparation method of bimetallic catalysts generally can be divided into two categories: (1) the bi-metal was first prepared and then supported on the carrier [25]; (2) the bi-metal as formed in the preparation progress [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…Ambient pressure X-ray photoelectron spectroscopy (AP-XPS) and environmental transmission electron microscopy (ETEM) showed that Pt migrates on the catalyst surface, and Pt aids the reduction of Co to its metallic state under appropriate reaction conditions confirmed by near edge X-ray absorption fine structure (NEXAFS) spectroscopy [25]. [27]. Similarly, they also found that Fe-Mo/Al 2 O 3 catalyst synthesized by the impregnation method is an efficient catalyst with high CO yield, almost no by-products and relatively stable (60 h) for the RWGS reaction.…”
Section: Methodsmentioning
confidence: 99%